Vanishing Point: Joan Didion and the Horizons of Historical Knowledge - Kenneth Millard (European Journal of American Studies)
This critical study situates Joan Didion’s memoir Where I Was From in the context of debates about the textuality of history in contemporary culture. In particular the essay is a critical examination of Didion’s interest in the concept of origins. What are the politics of historical origins, how might “true origins” be known, and how might a different understanding of such origins facilitate a feminist appraisal of Western American history? The essay argues that Didion’s book is an innovative contribution to the genre of the memoir, and to the social history of California and the American West.